Graft‐to‐recipient weight ratio threshold adjusted to the model for end‐stage liver disease score for living donor liver transplantation. Issue 12 (December 2016) - Alim, Altan; Erdogan, Yalcin; Yuzer, Yildiray; Tokat, Yaman; Oezcelik, Arzu
Abstract : The graft‐to‐recipient weight ratio (GRWR) is an important selection criterion for living donor liver transplantation (LDLT). The generally accepted threshold is known to be 0.8%. We believe that this threshold can be reduced under certain conditions. The aim of this study was to evaluate the results of these patients with GRWR < 0.8%. Between 2004 and 2015, 649 patients underwent right lobe LDLT for end‐stage liver disease in adult patients. All recipients who had GRWR < 0.8% were identified. The data of these patients were retrospectively analyzed and compared to patients with GRWR ≥ 0.8%. There were 43 patients with GRWR < 0.8%. Out of these patients, 7 (16%) had GRWR of 0.6%. The median Model for End‐Stage Liver Disease (MELD) score was 15, and the median donor age was 30 years. Anterior segment drainage was ensured. Portal inflow modulation was performed by splenic artery ligation according to the portal flow. Postoperative complications were seen in 6 (14%) patients. Of all 43 patients, 3 (7%) died perioperatively within 1 month, and 1 (2%) patient underwent retransplantation due to graft failure. The mean hospital stay was 18 days. The 1‐year survival rate was 93%. None of the patients had a laboratory MELD score above 20. The comparison of the results with the patients who had GRWR ≥ 0.8% has shown no significant difference, except MELD score, body mass index (BMI), and rate of anterior segment drainage. The GRWR can be decreased even to 0.6% if the MELD score is below 20, donor age is below 45 years, and there are no signs for any hepatosteatosis of the donor graft. In these patients, it is essential that the anterior segment drainage is secured and the portal inflow modulation is performed according to the portal flow. Liver Transplantation 22 1643–1648 2016 AASLD .